Evaluasi Pelaksanaan Akomodasi Kurikulum untuk Peserta Didik dengan Hambatan Penglihatan pada Pelajaran Sosiologi - Andhy Surya Hapsara (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
Implementing curriculum accommodations through learning intervention is critical to supporting learning and special programmes in sociology lessons for students with special needs in class X. The objective of this work is to describe the evaluation of learning intervention for students with visual impairments in order for them to be agile in social mobility and communication orientation (OMSK) and skilled in learning sociological paradigms as part of curriculum accommodation that has been carried out. This study applied a descriptive qualitative method based on the Context-Input-Proccess-Product-Outcome (CIPPO) evaluation model, with data collected through interviews, observations, and document evaluation. The learning material was sociological paradigm that was carried out using several methods, including the observation method assisted by peer reporting to analyse the social facts paradigm; the action motive interview method to analyse the social definition paradigm; and reward type interviews to determine the social behaviour paradigm. The results of this study highlighted the successful implementation of curriculum accommodation as observed through the CIPPO technique, with all components completed. The impact of curriculum accommodation is an improvement in OMSK, for example, the special needs student is more agile for getting around the school. Furthermore, the special needs student is skilled at conducting well-mannered and polite interviews with teachers or staff members at school.